Preparation of Highly Cross-linked Magnetic Polymer Composite Particles and Application in the Separation of Arsenic from Water - Sharafat, M. K.; Ahmad, H.; Alam, M. A.; Rahman, M. M. (Rajshahi University Journal of Science and Engineering, 2016)
Iron oxide magnetic particles have become a promising research field in separation technology because of their easy separation by external magnetic field and can be applied for the removal of toxic metals from waste water. Highly cross-linked Fe3O4/P(S-DVB) particles were prepared in this research by suspension polymerization of styrene (S) and divinylbenzene (DVB) in presence of nanosized Fe3O4 particles. At first Fe3O4 nanoparticles were prepared by co-precipitation of Fe2+ and Fe3+ from their alkaline aqueous solution. To stabilize the magnetic particles, the surface of the particles was modified with oleic acid. The morphology and surface structure were characterized by Fourier Transform IR(FTIR), Transmission Electron Microscope (TEM), Scanning Electron Microscope(SEM), and light microscope.The adsorption behavior of As(III) on composite polymer particles was evaluated and a comparative study with reference copolymer particles revealed that composite polymer particles possessed better adsorption capacity.